Protection against Clostridium difficile infection in a hamster model by oral vaccination using flagellin FliC-loaded pectin beads. Issue 40 (25th September 2018) - Bruxelle, J.F.; Tsapis, N.; Hoys, S.; Collignon, A.; Janoir, C.; Fattal, E.; Péchiné, S.
Abstract: Clostridium difficile flagellin FliC is a highly immunogenic pathogen-associated molecular pattern playing a key role in C. difficile pathogenesis and gut colonization. Here, we designed an oral vaccine against C. difficile with FliC encapsulated into pectin beads for colonic release. Bead stability and FliC retention was confirmed in vitro using simulated intestinal media (SIM), while bead degradation and FliC release was observed upon incubation in simulated colonic media (SCM). The importance of FliC encapsulation into pectin beads for protection against C. difficile was assessed in a vaccination assay using a lethal hamster model of C. difficile infection. Three groups of hamsters orally received either FliC-loaded beads or unloaded beads in gastro-resistant capsule to limit gastric degradation or free FliC. Two other groups were immunized with free FliC, one intra-rectally and the other intra-peritoneally. Hamsters were then challenged with a lethal dose of C. difficile VPI 10463. Fifty percent of hamsters orally immunized with FliC-loaded beads survived whereas all hamsters orally immunized with free FliC died within 7 days post challenge. No significant protection was observed in the other groups. Only intra-peritoneally immunized hamsters presented anti-FliC IgG antibodies in sera after immunizations. These results suggest that an oral immunization with FliC-loaded beads probably induced a mucosal immune response, therefore providing a protective effect. This study confirms the importance of FliC encapsulation into pectin beads for a protective oral vaccine against C. difficile .